2019
DOI: 10.3390/nu11020292
|View full text |Cite
|
Sign up to set email alerts
|

Insect Consumption Attitudes among Vegans, Non-Vegan Vegetarians, and Omnivores

Abstract: Background: Consumption of foods of insect origin is encouraged, since insect consumption is seen as one of the responses to the environmental impact of meat production. This study examines the attitude (A), subjective norm (SN), perceived behavioral control (PC), and food neophobia (FN) toward the consumption of foods of insect origin, as well as the conditions for eating insect-based foods among vegans, vegetarians, and omnivores. Methods: The data was obtained by using an online survey and convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
1
53
1
Order By: Relevance
“…Rather, it may affect food categories that people are already used to eating, such as flour-based or highly processed foods. This contrasts with the findings of the survey conducted by Elorinne [77], which indicated that products of non-animal (i.e., vegetable) origin trigger lower levels of food neophobia than animal-based products. Food neophobia seems to be an extremely complex attitude.…”
Section: Neophobia and Attitude Towards New Foodscontrasting
confidence: 94%
See 2 more Smart Citations
“…Rather, it may affect food categories that people are already used to eating, such as flour-based or highly processed foods. This contrasts with the findings of the survey conducted by Elorinne [77], which indicated that products of non-animal (i.e., vegetable) origin trigger lower levels of food neophobia than animal-based products. Food neophobia seems to be an extremely complex attitude.…”
Section: Neophobia and Attitude Towards New Foodscontrasting
confidence: 94%
“…However, for some subcategories of novel food-such as genetically modified and functional foods -the relationship between the consumer's attitude and food neophobia may not be straightforward [67]. Furthermore, less conventional food choices, such as a vegan diet, can also result in high neophobia scores, as Elorinne's survey found [77]; this does not shed light on the reasoning behind the type of choice. The construct thus appears to be poorly defined, as it is very elastic and could encompass food philosophies that are very distant from each other.…”
Section: What Do Neophobia Scores Actually Measure?mentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes concerning the eating of insects were studied in Finland among vegans, vegetarians, and omnivores (Elorinne et al, 2019). Non-vegan vegetarians held the most positive attitude toward eating insects, mainly because of sustainability reasons, also an important argument for omnivores.…”
Section: Consumer Attitudesmentioning
confidence: 99%
“…A recent study by Elorinne et al [49] showed how vegans, non-vegan vegetarians, and omnivores hold different intention regarding eating insects. In particular, non-vegan vegetarians held the most positive attitude toward entomophagy, whereas vegans felt more strictly that it was morally wrong to include edible insects (i.e., meat consumption) as an eating practice.…”
Section: Vegetarians and Entomophagymentioning
confidence: 99%